INVESTIGATION OF STRUCTURAL AND OPTICAL PROPERTIES OF Sb2S3 THIN FILMS - Shaban, Salma M (Al-Nahrain Journal of Science, 2010)
Sb2S3 thin films were obtained by evaporating the powder of Sb2S3 compound onto glass substrates maintained at room temperature and at substrate temperature 423 K under vacuum pressure of (2 10-5) torr. The composition of Sb2S3 powder was determined by atomic absorption spectroscopy .The deposited films at room temperature were amorphous but the deposited films at 423K were polycrystalline structure. Optical parameters like absorption coefficient, energy gap, and refractive index were measured by the analysis of the experimental transmission spectrum over the wavelength range (200-1100) nm.